The Impact of Bad Credit on Debtor and Creditor Accountability in Fiduciary-Based Bussiness Financing - Sondang, Monica Berliana (Golden Ratio of Finance Management, 2025)
Bad credit, which late payments by the debtor characterize, can damage the relationship of trust between the two parties and increase the Non-Performing Loan (NPL), which affects the financial health of the Pegadaian company. The method used in this research is descriptive analysis with a qualitative approach, which involves systematic observation, in-depth interviews, and literature studies to collect information and data relevant to the research discussed. The results of this study indicate that debtor accountability is strongly influenced by their ability to fulfill payment obligations. At the same time, creditors need to analyze business feasibility and efforts to mitigate risks so that non-performing loans do not increase. This research emphasizes the importance of clearly understanding each party's obligations, the debtor and the creditor bound by the fiduciary, to benefit both parties. Thus, it is expected to create a sustainable financing environment, which can increase economic growth in Samarinda.